Through Laser Scanned Point Clouds to Techno-Sight and a Landscape on the Move. Issue 1 (2nd January 2017) - Nordström, Paulina
Abstract : Three-dimensional (3D) laser scanning is a geovisual technology used for precision scientific measurements and 3D representations of reality. Laser scanning technology produces point clouds, which are extraordinary kinds of images: commonly a combination of the laser beams' journey between the scanner and the materialities of a site, and the photographs. In this article, I examine the confused surfaces of point clouds by focusing on the encounter between the laser scanner and moving objects. This encounter is registered as a figure without resemblance, which I call the chimeric point cloud. The chimeric point cloud is oriented toward the past and the future. Using this example, and drawing on Deleuze's surface event, I broaden the notion of nonrepresentational landscape theory to a consideration of an absence of both the past and future. I show how digital images and technology affect the landscape sight at future sites of encounter through generating sensations.